The Effect of Edmodo on Students’ Intrinsic Motivation - Kahar, Siti Rahmawati (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study was to determine how using Edmodo as a computer-based learning (Call activity) affected students' intrinsic motivation to learn English. The study focused on this approach. The objective of this research was twofold: on the one hand, it directed to examine the effect of Edmodo on students’ intrinsic motivation in learning English; on the other hand, it tried to identify the best learning activities that could positively affect students’ intrinsic motivation in learning English. Total participant were 27 students. Sample were using the purposive sampling technique. The study adopted a mixed method. Paired sample t-test was run to reveal the impact of Edmodo on students’ intrinsic motivation. Results of the study show that there was no significant effect of Edmodo on students’ intrinsic motivation. This discrepancy was possibly caused by a number of factors, including the students’ perception toward Edmodo, technology, characteristics of language skills, and design of learning activities